2000
DOI: 10.1159/000007773
|View full text |Cite
|
Sign up to set email alerts
|

End Expiration Is More Accurate than Mid Respiration in Measuring Lower Esophageal Sphincter Pressure

Abstract: Background/Aims: Two ways popularly used to measure lower esophageal sphincter pressure are the mid-respiratory and end-expiratory methods. The aim of this study was to compare the suitability of these methods in the manometric assessment of patients with endoscopically documented esophagitis. Methods: Manometry was performed on 22 consecutive patients to determine whether medical therapy or surgery was the more appropriate treatment strategy. Lower esophageal sphincter pressure was measured during a slow stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
3
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
(11 reference statements)
2
3
0
Order By: Relevance
“…This study has demonstrated that the LES pressure is lower during end‐expiration compared with inspiration during spontaneous breathing in awake, obese individuals. This is in agreement with results from studies in normal‐weight patients 3 . Consequently, it would seem relevant to use end‐expiratory values for LES measurements in order to record the lowest pressure.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This study has demonstrated that the LES pressure is lower during end‐expiration compared with inspiration during spontaneous breathing in awake, obese individuals. This is in agreement with results from studies in normal‐weight patients 3 . Consequently, it would seem relevant to use end‐expiratory values for LES measurements in order to record the lowest pressure.…”
Section: Discussionsupporting
confidence: 89%
“…Authors of gastroenterological studies recommend measuring the LES pressure during expiration based on the variation in the esophageal pressure during respiration 3 . In most anesthesiology reports, no data are presented regarding the phase of the respiratory cycle in which the measurements have been carried out.…”
mentioning
confidence: 99%
“…The degree of intrinsic sphincter closure appears to vary with the rate, depth, or volitional modification of inspiration. The LES and IUS pressure responses seen in this study appear similar to the “respiration artifacts” in other studies . It is possible that the IUS closure and pressure elevation related to inspiration could give a structural advantage at the neck of the urinary bladder to prevent incontinence (Fig.…”
Section: Discussionsupporting
confidence: 78%
“…Previous work has referred to transient relaxation or inhibition of the LES in association with swallowing, obstructive sleep apnea, mechanical ventilation, and a negative pressure body ventilator . In previous animal and human studies, respiration pressure “artifacts” in the LES and IUS were not noted or were electronically filtered by manometry instruments . There may be respiratory influences on intrinsic sphincter function that have not been adequately evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…17 With the mouths closed, increasing flow rates demonstrated nonlinear increases in airway pressure but airway pressures remained below 10 cmH 2 O even with flow rates up to 80 l min À1 . 17 As the threshold pressure to overcome the LOS is approximately 15 to 25 mmHg (20 to 34 cmH 2 O), 18 the increase in upper airway pressure by the THRIVE technique should be insufficient to induce gastric insufflation with its attendant risk of subsequent regurgitation.…”
Section: Discussionmentioning
confidence: 99%